Neutron Diffraction Measurements for Residual Stresses in AL-6XN Stainless Steel Welded Beams - Cheng, Xiaohua; Prask, Henry J.; Gnaeupel-Herold, Thomas; Luzin, Vladimir; Fisher, John W. (IntechOpen, 2012)
None